2015
DOI: 10.3390/atmos6030234
|View full text |Cite
|
Sign up to set email alerts
|

Summertime Spatial Variations in Atmospheric Particulate Matter and Its Chemical Components in Different Functional Areas of Xiamen, China

Abstract: Due to the highly heterogeneous and dynamic nature of urban areas in Chinese cities, air pollution exhibits well-defined spatial variations. Rapid urbanization in China has heightened the importance of understanding and characterizing atmospheric particulate matter (PM) concentrations and their spatiotemporal variations. To investigate the small-scale spatial variations in PM in Xiamen, total suspended particulate (TSP), PM10, PM5 and PM2.5 measurements were collected between August and September in 2012. Thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…These values are comparable to the results from European background sites, which reported that EC wet deposition fluxes ranged from 0.4 to 3.2 mgC·m −2 ·month −1 and that WIOC fluxes ranged from 5.1 to 31.5 mgC·m −2 ·month −1 [6]. The atmospheric OC and EC concentrations in Xiamen were comparable to the urban background sites in Europe [27], which indicated comparable deposition fluxes. EC wet deposition fluxes in snow in northeastern China were estimated to be 4.…”
Section: Wet Deposition Fluxessupporting
confidence: 85%
See 2 more Smart Citations
“…These values are comparable to the results from European background sites, which reported that EC wet deposition fluxes ranged from 0.4 to 3.2 mgC·m −2 ·month −1 and that WIOC fluxes ranged from 5.1 to 31.5 mgC·m −2 ·month −1 [6]. The atmospheric OC and EC concentrations in Xiamen were comparable to the urban background sites in Europe [27], which indicated comparable deposition fluxes. EC wet deposition fluxes in snow in northeastern China were estimated to be 4.…”
Section: Wet Deposition Fluxessupporting
confidence: 85%
“…The TOT method follows the National Institute for Occupational Safety and Health (NIOSH) protocol [32]. The details of the TOT method can be found elsewhere [26,27]. Briefly, the small piece of the filter is gradually heated in pure helium (He) gas environment to 850 • C at which point most organic carbon is thought to be converted into carbon dioxide (CO 2 ), whereas small organic compounds are charred into EC.…”
Section: Sampling and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is suggested that if water-soluble fraction of aerosols does not show significant contribution from seasalts and soluble dust then, as a first approximation, it can be considered as the water-soluble secondary fraction of aerosols (both inorganic and organic) present in the atmosphere over a given region. (Ram and Sarin, 2011); Xiamen: representing a clean city in China (Zhao et al, 2015); and (Lecce: representing urban background site in Italy ) are also presented in Table 2. The contribution of WSS to PM 2.5 i.e., water-soluble secondary aerosol fraction varied from 0.30 to 0.62 during the year with the highest contribution during winter and spring (55e60%) followed by autumn (~45%) whereas, minimum (~30%) during summer and wet seasons (Table 2).…”
Section: Water-soluble Fraction Of Aerosolsmentioning
confidence: 99%
“…However, it may present potential hazard to human and the environment hence the presence of various toxic elements in the fallout dust. Acute and chronic health effects are related to the in halable PM 10 exposure in the urban environment [4] including acute respiratory related conditions (asthma, acute bronchitis, running nose) cerebrovascular disease (stroke), respiratory diseases, cardiopulmonary disorders, ischemic heart disease [19], damage of vital organs such as kidneys, liver and gastrointestinal system [20], different cancer, mortality and reduction in life expectancy, admission in hospitals and regular health [21]. Similar to dust, PM suspended in the atmosphere leads to visibility degradation.…”
Section: Pm 10 Real Time Measurementsmentioning
confidence: 99%